DIGITAL TRANSFORMATIONS EFFECT ON RAISING THE EFFICIENCY OF INFORMATION PROJECT MANAGEMENT: AN ANALYTICAL STUDY (American Journal of Research in Humanities and Social Sciences, 2026)
The study aims to diagnose the reality of digital transformation in the Central Library, and measuring its effect on enhancing the efficiency of information project management in its technical and human dimensions. It also seeks to identify barriers to access to the smart library and to provide a practical model that contributes to automating office processes and raising the accuracy of information retrieval, the descriptive-analytical approach was adopted in the study and the questionnaire, observation and standardized interview were used as methods of data collection, and the statistical program SPSS version 23 was used to analyze the results of the study, and the study came out with a number of results, most notably: The Central Library has achieved remarkable success in the project of the digital repository for dissertations, as it obtained the highest average of (4.42), making it the most efficient project, the results proved that digital transformation has actually contributed to reducing the time spent on academic research and improving the accuracy of information retrieval, existing digital systems have achieved a good level of ensuring the sustainability of available resources without significant technical disruption, despite the need to upgrade infrastructure.